2011
DOI: 10.1002/eji.200940188
|View full text |Cite
|
Sign up to set email alerts
|

C‐type lectin SIGNR1 enhances cellular oxidative burst response against C. albicans in cooperation with Dectin‐1

Abstract: We investigated the role of SIGNR1 in the recognition of Candida albicans and the subsequent cellular oxidative burst response. Soluble SIGNR1 (sSIGNR1) tetramer bound equally to zymosan and both heat-killed (HK) and live C. albicans in an EDTA-sensitive manner, whereas sDectin-1 tetramer predominantly bound to zymosan and HK-microbes in an EDTA-independent manner. In cellular response, enhanced oxidative burst was observed in RAW264.7 cells expressing SIGNR1 (RAW-SIGNR1) compared with RAW-control cells upon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 40 publications
1
26
0
1
Order By: Relevance
“…We also confirmed that macrophage recognition of zymosan was laminarin sensitive in the absence of LPS but laminarin insensitive for LPS-primed cells [22]. Zymosan particles are composed primarily of betaglucan, and cell surface macrophage PRRs reported to bind to this carbohydrate include Dectin-1 [25], CR3 [26], SIGNR1 [27], scavenger receptors [28], and lactosylceramide [29]. The mannose receptor has also been implicated as a PRR for zymosan via recognition of mannan on these particles [30].…”
Section: Discussionsupporting
confidence: 75%
“…We also confirmed that macrophage recognition of zymosan was laminarin sensitive in the absence of LPS but laminarin insensitive for LPS-primed cells [22]. Zymosan particles are composed primarily of betaglucan, and cell surface macrophage PRRs reported to bind to this carbohydrate include Dectin-1 [25], CR3 [26], SIGNR1 [27], scavenger receptors [28], and lactosylceramide [29]. The mannose receptor has also been implicated as a PRR for zymosan via recognition of mannan on these particles [30].…”
Section: Discussionsupporting
confidence: 75%
“…CLRs, particularly SIGNR1, expressed by phagocytes (e.g., DCs) are critical pattern-recognition receptors interacting with microbial carbohydrate recognition domains (CRDs) (87) to efficiently internalize and phagocytize microbes in concert with other molecules, including complement receptors (88), and to potentiate the oxidative responses to pathogens (e.g., Candida albicans) via dectin-1/SyK-dependent signaling (89). One can speculate that the signaling pathways of SIGNR1 involve regulated immune complexes (e.g., SOCS1) whose activation may be dependent on a mannosylated S-layer binding to SIGNR1 to control proinflammation in DCs that influence regulatory Th17 cells (90,91).…”
Section: Methodsmentioning
confidence: 99%
“…Soluble lectin (sLectin) tetramers, such as sSIGNR1 and shDC-SIGN, were prepared as described previously (26). Briefly, cDNA fragments encoding their extracellular domains were cloned into pEXPR-IBA44 (IBA, Göttingen, Germany) to add N-terminal BM40 secretion signal and Strep-Tag II sequences, followed by transfer into pEF6/V5-His (Invitrogen).…”
Section: Cells and Culturesmentioning
confidence: 99%